Preparation and characterization of LiNiVO4 and LiNi1-x MnxVO4 (0≤ x ≤1) cathode materials / Leena Ismail - Ismail, Leena (2012)
The inverse spinel lithium nickel vanadate, LiNiVO4 and doped system lithium nickel manganese vanadate, LiNi1-xMnxVO4, x = 0.25 having cubic structure were successfully synthesized by the sol- gel (SG) and polymer precursor (PP) method. The citric acid was used as the chelating agent for both techniques. The TGA analysis was carried out to estimate the suitable firing temperature of the dried precursor and to investigate the chemical reaction during the synthesized process. All prepared system namely LiNiVO4- SG, LiNiVO4- PP, LiNi0.75Mn0.25VO4- SG, and LiNi0.75Mn0.25VO4- PP was calcined at temperature range from 500 C to 800 C for 3 hours separately in a furnace. The firing environment was done in air. The reducing agent used and the distilled water used as the solvent had made the synthesizing process simple and yet economical. The reaction mechanism of the LiNiVO4- SG agrees with the thermal analysis for decomposition process. The XRD pattern of the LiNiVO4- SG sample show an absence of the NiO impurities starting at 600 C to 800 C. The single phases of pure inverse spinel product were obtained at all sintering temperatures for LiNiVO4- PP, LiNi0.75Mn0.25VO4- SG, and LiNi0.75Mn0.25VO4- PP systems. The Scherrer equation has been implemented to calculate the crystallite size of the obtained powder in this work. The obtained values from the equation satisfy the observed TEM results obtained in this work. The nanosized range particle was achieved between 42.94 nm to 68.07 nm for the LiNiVO4- SG sample and 33.38 nm to 48.43 nm for the LiNiVO4- PP system. The doped LiNi0.75Mn0.25VO4- SG and LiNi0.75Mn0.25VO4- PP system was found to be in the range of 23.65 nm to 33.54 nm and 19.82 nm to 39.53 nm respectively. It can be conclude that the doping material and additional of the polymer source inhibit the grain iv growth of the particle in this work. The SEM morphology for the LiNiVO4- SG system reveals that the particle distribution having porous morphology of the highest firing temperature at 800 C. The formations of the polyhedral morphology were clearly seen as the samples were heated at elevated temperature for the LiNiVO4- PP, LiNi0.75Mn0.25VO4- SG, and LiNi0.75Mn0.25VO4- PP systems. The elemental study, EDAX for this work also agrees stoichiometrically with the prepared cathodes. The open circuit voltage was obtained for undoped LiNiVO4- SG and LiNiVO4- PP system at around 3.0 V - 3.5 V for the both doped LiNi0.75Mn0.25VO4- SG and LiNi0.75Mn0.25VO4- PP systems. The cyclic voltammetry employed for the Li/ Li+ system show reversible mechanism for the fabricated half- cell suggesting that the de/intercalation of Li+ ion took place in the cell system. The de/intercalation peak using the LiNiVO4- SG cathode demonstrate oxidation peak at 4.7 V and 4.3 V for the reduction peak. The anodic and cathodic peaks were observed at 4.4 V and 4.2 V respectively using the LiNiVO4- PP cathode. The voltammogram of the cell using the LiNi0.75Mn0.25VO4- SG show deintercalation peak at 4.3 V while at 3.7 V of reducing peak during the 1st scan. The oxidation peak at 4.4 V for the forward scan were observed and at 3.7 V of the reduction peak for cell using the LiNi0.75Mn0.25VO4- PP cathode.